Experimental Study of the Use of Modified Football Balls in Physical Education Learning on Students' Motivation and Active Participation - Sudirman, Sudirman (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This study aimed to analyze the effect of using modified football balls on students' learning motivation and active participation in Physical Education lessons at Kassi-Kassi Elementary School in Makassar City. The study used an experimental design with a pretest–posttest control group design, involving 30 students randomly divided into an experimental group (n = 15) and a control group (n = 15). The experimental group participated in football lessons using modified balls that were smaller, lighter, and softer in texture, while the control group used standard balls. The results showed that the use of modified balls significantly increased students' motivation and active participation. For the learning motivation variable, the experimental group experienced an average increase of 19.27 points, while the control group only increased by 6.26 points. Meanwhile, for the active participation variable, the experimental group increased by 22.40 points, compared to the control group's 7.40 points. Paired t-test results showed significant increases in each group, and independent sample t-test results showed a significant difference in motivation and participation between the two groups (p = 0.000). These findings confirm that modified football balls can create a safer, more enjoyable learning environment that aligns with the motor skills of elementary school students. The study concluded that equipment modification can be an effective strategy for increasing motivation and active participation in physical education (PE) learning and can be applied in school contexts with limited facilities.